Effects of Mannitol and Xylitol on the Quality of Spicy Wheat Gluten Sticks - Qiuyan Ren; Heng Yang; Ziyang Jia; Wenping Ding; Yang Fu; Shensheng Xiao; Yanmei Wei; Kaifeng Zhao; Yan Wu; Xuedong Wang (Journal of Food Quality)
The present study sought to evaluate the effects and mechanisms of mannitol and xylitol on the regeneration of spicy wheat gluten sticks (SWGSs) through texture profile analysis (TPA), Fourier-transform infrared spectroscopy (FTIR), differential scanning calorimetry (DSC), X-ray diffraction (XRD), and low-field nuclear magnetic resonance (LF-NMR). The rate constant of crystallization and the relative degree of crystallinity of SWGS substantially reduced with polyols addition after 4 weeks of storage at 4°C. The peaks near 3385 cm−1 and 1081 cm−1 in FTIR of SWGS became wider with the addition of mannitol and xylitol, indicating that mannitol and xylitol formed hydrogen bonds by binding to wheat starch. The DSC experiment results showed that the addition of mannitol and xylitol could reduce the Tp and ΔH of SWGS powder effectively under different storage times. The NMR results showed that the water in SWGS was mainly immobile water, and the addition of mannitol and xylitol could increase the content of bound water and immobile water in SWGS and reduce the water migration. These results provided deeper insights into the action mechanism of mannitol and xylitol in delaying the quality change of starch products during storage, thereby providing a reference for inhibiting SWGS regeneration. Therefore, it could be inferred that improving the quality of SWGS by adding polyol might have significant application prospects in the food industry.